Dosimetric evaluation of radiation treatment planning for simultaneous integrated boost technique using monte carlo simulation - Ravindra Shende; S J Dhoble; Gourav Gupta (Journal of Medical Physics, 2023)
Monte Carlo (MC) techniques have been recognized as the gold standard for the simulation of radiation transport in radiotherapy. The aim of the study is to perform dosimetric evaluation of Simultaneous Integrated Boost (SIB) radiation treatment planning using MC simulation approach. The geometrical source modeling and simulation of 6 MV Flattening Filter Free (FFF)beam from TrueBeam linear accelerator have been carried out to simulate Volumetric Modulated Arc Therapy (VMAT) plans using MC simulation software PRIMO. All the SIB plans have been generated using VMAT techniques for patients with locally advanced postoperative head-and-neck squamous cell carcinoma in Eclipse Treatment Planning System (TPS) retrospectively. TPS plans have been compared against their respective MC-simulated plans in PRIMO. The quality assessments of plans have been performed using several dose volume parameters, plan quality indices, and methods of gamma analysis. Dmean, D50%, and D2% received by planning target volume (PTV), PTV60, and PTV52 have been found significantly lower in TPS-generated plans compared to MC-simulated plans. D100%, D98%, and D95% received by PTV60 exhibit good agreement. However, PTV52 shows a significant deviation between TPS and MC plans. The mean organ-at-risk doses have been found significantly lower in TPS plans compared to MC plans. TPS and MC plans have been found in close agreement within gamma acceptance criteria of 3% Dose Difference (DD) and 3 mm Distance to Agreement (DTA). Dose distributions computed using MC simulation techniques are reliable, accurate, and consistent with analytical anisotropic algorithm. Plan quality indices have been found slightly compromised in MC-simulated plans compared with TPS-generated plans appeared to be a true representation of real dose distribution obtained from MC simulation technique. Validation using MC simulation approach provides an independent secondary check for ensuring accuracy of TPS-generated plan.